Socio-Economic Heterogeneity and Electoral Turnout: An Aggregate Analysis with Precinct-Level Data - Giorgio Bellettini; Carlotta Berti Ceroni; Chiara Monfardini (Center for Economic Studies and ifo Institute (CESifo), 2014)
In this paper we perform an empirical analysis to investigate the impact of socio-economic heterogeneity on electoral turnout. We exploit a unique dataset on local elections in an Italian municipality, which merges information on socio-economic characteristics of about 370.000 individuals with turnout data at the precinct level in 2004 and 2009. Controlling for unobserved precinct-specific fixed effects, we find that electoral turnout is not affected by income inequality. We also document a negative effect on electoral participation of the share of immigrants, population density, and the share of singles. These results suggest that increased ethnic heterogeneity and reduced social pressure tend to depress turnout.
Keywords: D72; 330; income inequality; electoral turnout; heterogeneity